Stressful life events and Low birth Weight: according to social determinant of health approach - Mahmoodi, Zohreh; Karimlou, Masoud; Sajjadi, Homeira; Dejman, Masoumeh; Vameghi, Meroe; Dolatian, Mahrokh (Advances in Nursing & Midwifery, 2016)
Background and aim: Stressful life events during pregnancy are associated with adverse consequences for mother and newborn. The purpose of this study was to understand the effects of stressful life events during pregnancy on low-birth-weight newborn according to social determinants of health. Materials and Methods: This study was the second part of a large research project. The main study was conducted using case-control design. Samples were recruited in four stages by selecting 750 mothers with newborns weighing less than 4000 gr using multistage sampling method. The data about women’s lifestyle during pregnancy was collected using a questionnaire which was developed using inductive and deductive approaches based on social determinants of health. This study assessed stressful life events during pregnancy using 18 items Findings: The average of stressful life events number and the total score of this domain were different between two groups (p<0.001). The odds ratio for effect of a one-unit increase in stress score, increased the risk of low- birth-weight by 1.03 times (p=0.001). Conclusion: The stressful life events can influence fetal growth independently. Although receiving health care during pregnancy (the biological dimension), has an important influence, the role of stress, the related factors and the coping methods should be considered. Keywords: Stressful Event; Social Determinant of Health; Newborn, Infant, Low Birth Weight